Effects of Concrete Core Technological Defects on the Strength of Tube Confined Concrete Elements - Semko, Oleksandr; Gukasian, Olga; Skliarenko, Serhii (International Journal of Engineering and Technology, 2018)
The paper sums up a series of experimental studies describing the influence of most types of concreting common defects, such as core weakening: weak compression inclusions, voids, height heterogeneity of concrete. The basis of the experimental study is the research on the concrete core production conditions influence on tube confined concrete elements and the change in physical and mechanical characteristics of the elements. The concrete strength is estimated based on the results of the study of specially shaped samples with given dimensions. According to the results of concreting samples with different types of modeled defects (abnormalities) inspection, the most dangerous damages of the concrete core were identified and different variants of the height strength retrogression of the elements under study were analyzed. As a result, the degree and type of damage to the tube confined concrete elements core of the samples, which affect the fracture pattern, was established. Â